The World Affairs Companion : The Essential One-Volume Guide to Global Issues - Segal, Gerald, 1953- (London Simon & Schuster, 1993)
This facts-at-your-fingertips book combines compact histories of the enduring conflicts of the 20th century with up-to-date assessment of pivotal issues, people and regions. It provides analysis of topics from nuclear proliferation to the environment.
Include Map, Tables and Index
Keywords: World politics -- Internationale Betrekkingen